A Practical Experiment on a Growing Baby in Bangladesh: A Model of Teaching and Learning Arabic in a Non-Native Environment - Md. Masudur Rahman; Saud Bin Mohammad (Universiti Sains Islam Malaysia, 2025)
Al-Azkiyaa - International Journal of Language and Education, Volume 4 Issue 1 Page (113–124)